Content Analysis of MAFINDO's Verified WhatsApp-Related Misinformation in Indonesia - Rahmawan, Detta; Garnesia, Irma; Hartanto, Rudi (School of Journalism, Faculty of Communication Sciences, Universitas Padjadjaran, 2024)
This study seeks to contribute to the emerging studies on fact-checking practices in the Global South by focusing on Indonesia, one of the largest democratic countries in the world. An organization and grassroots movement called MAFINDO (Masyarakat Anti Fitnah Indonesia/the Indonesian Anti-Defamation Society) has been spearheading fact-checking practices in Indonesia by operating a website “turnbackhoax.id” containing fact-checked articles including on misinformation spread through WhatsApp. This research uses content analysis to examine a diverse array of WhatsApp-related misinformation verified by MAFINDO, spanning from July 2015 to July 2020. Our findings reveal that politics and everyday occurrences, or trivial issues top the charts of WhatsApp-related misinformation, with nearly half primarily existing in the text format. Notably, the originators of this misinformation remain unknown, and MAFINDO primarily utilizes news articles for verification. Furthermore, we assess the